HYDROGEN ISOTOPE RATIOS OF RECENT LACUSTRINE SEDIMENTARY N-ALKANES RECORD MODERN CLIMATE VARIABILITY - Sachse D.; Radke J.; Gleixner G. (My University, 2004)
Hydrogen isotope ratios were measured on n-alkanes (n-C12 to n-C31) extracted from recent lake surface sediments along a N-S European transect to test if modern climate variability is recorded in these biomarkers. δD values of the n-alkanes are compared to δD values of meteoric water from the IAEA-GNIP database spanning a range from −119‰ in northern Sweden to −41‰ in southern Italy, to lake water δD values, and to mean annual temperatures, varying between −2.0°C in the north and 13.7°C in the south.